2011
DOI: 10.1007/s10495-011-0631-z
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin triggers apoptotic signaling pathways and autophagic survival response in human colon adenocarcinoma cells and their derived metastatic cells

Abstract: Silibinin, a flavonolignan isolated from the milk thistle plant (Silybum marianum), possesses anti-neoplastic properties. In vitro and in vivo studies have recently shown that silibinin inhibits the growth of colorectal cancer (CRC). The present study investigates the mechanisms of silibinin-induced cell death using an in vitro model of human colon cancer progression, consisting of primary tumor cells (SW480) and their derived metastatic cells (SW620) isolated from a metastasis of the same patient. Silibinin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 41 publications
3
56
0
1
Order By: Relevance
“…Several studies showed that silibinin induced apoptosis via increased Bcl-2 family levels, and reduced antiapoptoticmolecules in different carcinoma cells models (Kauntz et al, 2011;Hagelgans et al, 2014). How silibinin induced cell death and associated signal pathway of apoptosis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that silibinin induced apoptosis via increased Bcl-2 family levels, and reduced antiapoptoticmolecules in different carcinoma cells models (Kauntz et al, 2011;Hagelgans et al, 2014). How silibinin induced cell death and associated signal pathway of apoptosis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…V případě CRC in vitro zkoumání na různých liniích lidského adenokarcinomu prokázalo působení silymarinu na několika úrovních -snížení viability nádorových buněk, zastavení buněč-ného cyklu na různé úrovni dle buněčné linie [14], snížení hladiny cyklinu D1 v buňce indukcí jeho proteazomální degradace [15] a navození apoptózy vnitřní i zevní cestou, a to i u TRAIL (TNF-related apoptosis-induc ing ligand) -rezistentních mutant [16,17]. In vivo studie na potkanech zkoumaly efekt podá-vání per os silymarinu po vystavení kancerogennímu azoxymethanu, který navozuje vznik adenokarcinomu v oblasti kolon.…”
Section: Protinádorové účInky Silymarinu Prokázané V Preklinických Stunclassified
“…Silibinin-mediated angiogenesis inhibition was associated with decreased VEGF, cyclooxygenase (COX), hypoxiainducible factor-1α (HIF-1α), inducible nitric oxide synthase (iNOS), nitrotyrosine and nitrite levels, and an increased VEGFR-1 (Flt-1) expression (41,(43)(44)(45). Silibinin inhibited CDK8 and β-catenin signaling which inhibited SW480 tumor growth (46) and initiated an autophagic-mediated survival response in SW480 and SW620 cells (47). Silibinin also suppressed 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis in rat models via modulating xenobiotic metabolizing enzymes and increasing enzymatic antioxidants to detoxify carcinogens (48,49).…”
Section: Broad Spectrum Cancer Chemopreventive Efficacy Of Silibininmentioning
confidence: 99%